The symbolic materiality of land from a gender lens: an intersectional analysis of Mapuche women's oppressions, struggles and political strategies. - Ibarra, María Ignacia; Olga Jubany (Journal of Iberian & Latin American Studies, 2024)
From the anthropological tradition of ethnography, this paper adopts a feminist, intersectional and decolonial approach to expose the multiple edges of the experiences and political practices of Mapuche women, the care for their territory and struggle for the common good of their community. Grounded on an extensive empirical data, the paper analyses the relationship between the Mapuche people and the State of Chile, to reveal the impact this has had on the way Mapuche people develop as a community within their political spaces. Following this, the paper focusses on the diverse experiences of Mapuche women within their communities, exposing the impact of the processes of historical dispossession of the Mapuche territory, particularly as being a "Mapuche woman," as an identity based on lived and shared experiences and stories. The paper then examines representations of gender relations and gender violence, anchored on the binary order of the patriarchal and colonial system of the Global North. This exposes how Mapuche women occupy a place perceived as inferior to that of men, whilst it reveals how Mapuche women question these discursive constructions of colonial inheritance, to recover their history in their community configurations of equality.